2012
DOI: 10.3857/roj.2012.30.3.140
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemoradiotherapy for elderly patients with stage III non-small cell lung cancer

Abstract: PurposeCombined chemoradiotherapy is standard management for locally advanced non-small cell lung cancer (LA-NSCLC), but standard treatment for elderly patients with LA-NSCLC has not been confirmed yet. We evaluated the feasibility and efficacy of concurrent chemoradiotherapy (CCRT) for elderly patients with LA-NSCLC.Materials and MethodsAmong patients older than 65 years with LA-NSCLC, 36 patients, who underwent CCRT were retrospectively analyzed. Chemotherapy was administered 3-5 times with 4 weeks interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The difference in hospital admissions related to side effects was most prominent among the patients aged 70 years, possibly owing to the dose-reduced chemotherapy in this age group. Nevertheless, the rate of esophagitis and hematologic toxicity among the elderly were in accordance with the findings from Kang et al 34 They reported an incidence of treatment-related toxicity in the elderly that was noticeably lower than previously reported. 34 We should expect that more modern planning techniques and radiologic equipment will help to reduce the radiologic effects on the esophagus and bone marrow in the future.…”
Section: Elderly Poor Prognosis Patients and Palliative Concurrent Crtsupporting
confidence: 91%
“…The difference in hospital admissions related to side effects was most prominent among the patients aged 70 years, possibly owing to the dose-reduced chemotherapy in this age group. Nevertheless, the rate of esophagitis and hematologic toxicity among the elderly were in accordance with the findings from Kang et al 34 They reported an incidence of treatment-related toxicity in the elderly that was noticeably lower than previously reported. 34 We should expect that more modern planning techniques and radiologic equipment will help to reduce the radiologic effects on the esophagus and bone marrow in the future.…”
Section: Elderly Poor Prognosis Patients and Palliative Concurrent Crtsupporting
confidence: 91%
“…In clinical practice, not all patients are eligible for aggressive or radical treatment, especially elderly patients, 13 , 14 and treatment for those patients usually remains conservative. 8 , 15 In Driessen’s research, all patients received a minimum total tumor dose of 54 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it has been argued that fit, elderly patients with locally advanced NSCLC should receive a combined-modality therapy with cautious and judicious monitoring [ 6 , 11 ]. Growing evidence supports that aggressive treatment will have benefit in survival, even in elderly NSCLC patients [ 11 14 ]. But, it is obvious that elderly patients are generally not treated using a combined-modality therapy.…”
Section: Discussionmentioning
confidence: 99%